2020
DOI: 10.1039/c9mh01443h
|View full text |Cite
|
Sign up to set email alerts
|

All-weather-available, continuous steam generation based on the synergistic photo-thermal and electro-thermal conversion by MXene-based aerogels

Abstract: An all-weather steam generation system is achieved based on the alternative photo-thermal and electro-thermal conversion of crosslinked MXene aerogels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
107
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 176 publications
(108 citation statements)
references
References 66 publications
1
107
0
Order By: Relevance
“…The 2D Ti 3 C 2 nanosheets were synthesized via a method reported in our previous work. [ 52 ] First, the Ti 3 AlC 2 MAX phase with a layered morphology (Figure 1b ) was etched with LiF/HCl solution to remove the Al layers. Then, prolonged ultrasonic delamination was employed to obtain ultrathin Ti 3 C 2 nanosheets with reduced lateral dimensions for better uptake by cells.…”
Section: Resultsmentioning
confidence: 99%
“…The 2D Ti 3 C 2 nanosheets were synthesized via a method reported in our previous work. [ 52 ] First, the Ti 3 AlC 2 MAX phase with a layered morphology (Figure 1b ) was etched with LiF/HCl solution to remove the Al layers. Then, prolonged ultrasonic delamination was employed to obtain ultrathin Ti 3 C 2 nanosheets with reduced lateral dimensions for better uptake by cells.…”
Section: Resultsmentioning
confidence: 99%
“…To enhance the evaporation under weak sunlight, only very few studies have been reported by applying the photo-electro-thermal effect but did not take into consideration the salt-resistance and clean water collection performance. [15][16][17] Therefore, SI generators with excellent salt-resistance and all-weather high evaporation performance are greatly desired for practical solar desalination yet very challenging to develop. Generally, high evaporation performance and salt-resistance are constrained by each other.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the ever-worsening global warming, increasing global population, and steady improvement of life standards, adequate clean water and stable supply of clean energy with low carbon footprint are two key challenges for global sustainable development. [1][2][3][4][5][6][7][8] On the other hand, there is a vast amount of water constantly preserved in the Earth's atmosphere, generically known as atmospheric water, which is equivalent to six times all the water in all the rivers on Earth. 6,9 The capture-release of water vapor has underpinned a number of emerging designs significant to the water-energy nexus, such as sorption-driven heat transformation for cooling and heating, [10][11][12][13][14] atmospheric water harvesting (AWH), [15][16][17][18][19][20][21][22][23][24][25][26][27][28] vapor-sorption-based desalination, 14,29 and air humidity regulation.…”
Section: Introductionmentioning
confidence: 99%